STRENGTHENING THE ADMINISTRATION SYSTEM OF SCHOLARSHIP DATA COLLECTION BASED ON DIGITAL SERVICES TO ENCOURAGE GOOD ACCOUNTABILITY AND PROGRAM BENEFITS - Widyastuti, Ariyani; Prasandha, Diyamon (Universitas Negeri Semarang, 2025)
Scholarship programs have a strategic role in expanding access to higher education and improving the quality of human resources. However, at Universitas Negeri Semarang (UNNES), the scholarship administration system still faces a number of obstacles such as lack of data integration, delayed disbursement, and potential double funding. This study aims to analyze the condition of UNNES scholarship system management with PIECES (Performance, Information, Economic, Control, Efficiency, and Service) approach and evaluate the design of digital-based system in supporting the principle of good accountability. The method used is quantitative with questionnaire instruments and Importance Performance Analysis (IPA) analysis of 78 respondents from students, education personnel, and external parties. The results showed that all PIECES variables obtained satisfaction scores above 3.5 (category